Methodology for conducting linguistic research into visual impairment: Challenges and recommendations - Sak-Wernicka, Jolanta (LingBaW. Linguistics Beyond and Within, 2023)
Despite great value of research into visual impairment (VI), there is a dearth of empirical studies in linguistics investigating the extent to which the sense of seeing impacts language development, processing and production. The lack of methodological rigour in previous studies as well as large diversity of the population, small incidence of visual impairment and little awareness of blind people’s needs make this field of study challenging for researchers. This article presents and discusses the most challenging aspects of performing experimental studies in the field of VI. The overarching aim of this paper is to guide good research practice which ensures robust and unbiased experimental design and at the same time respects individuality of people with VI.